2009
DOI: 10.1111/j.1440-1746.2008.05699.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pro‐ and anti‐inflammatory cytokines in relation to apoptotic genes in Egyptian liver disease patients associated with HCV‐genotype‐4

Abstract: Aberrant expressions of AKT, GSK3-B, and BCL2 are common events in HCV-associated LD and HCC. AKT, GSK3-B and IL-6 are significantly associated with cirrhosis and could be used as biomarkers for both early detection and molecular target therapy for the prevention of HCC development. TNFRII, GSK3-B and s-AFP could be used as prognostic factors that can predict the clinical outcome of HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The intrahepatic mRNA levels of IFN-inducible T cell alpha chemoattractant (I-TAC), another CXCR3 chemokine ligand, correlate with both portal and lobular inflammation. Several investigators found that the intrahepatic CXCL10/IP-10 mRNA expression was associated with increased lobular necroinflammation (Harvey et al, 2003;Zekri et al, 2009). Our results showed overexpression of CXCR3 gene in 75% of HCC cases.…”
Section: Discussionsupporting
confidence: 68%
“…The intrahepatic mRNA levels of IFN-inducible T cell alpha chemoattractant (I-TAC), another CXCR3 chemokine ligand, correlate with both portal and lobular inflammation. Several investigators found that the intrahepatic CXCL10/IP-10 mRNA expression was associated with increased lobular necroinflammation (Harvey et al, 2003;Zekri et al, 2009). Our results showed overexpression of CXCR3 gene in 75% of HCC cases.…”
Section: Discussionsupporting
confidence: 68%
“…However, reduced expression of GSK3b (GSK3B), TNFa, TNF-R I, TNF-R II, and IL10 can be observed in HCC and in other liver diseases (Zekri et al 2009). It is also well accepted that estrogen functions as an immunomodulator with a bidirectional effect on cytokine production: at high concentrations, E 2 decreases the production of pro-inflammatory cytokines including TNFa and IL1b (ILB1) (Ito et al 2001, Hsieh et al 2007), whereas at low concentrations, it increases the production of TNFa and IL1b (Roby & Hunt 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There are more cases of HCV and endemic chronic HCV infection in Egypt than in any other country worldwide [6]. The highest prevalence rate worldwide has been reported in Egypt (15%), where HCV genotype-4 represented 90% of all HCV cases [5,7].…”
Section: Introductionmentioning
confidence: 99%